2003
DOI: 10.1046/j.1365-2036.17.s1.7.x
|View full text |Cite
|
Sign up to set email alerts
|

Esomeprazole 20 mg and lansoprazole 15 mg in maintaining healed reflux oesophagitis: Metropole study results

Abstract: Introduction: Esomeprazole, the first proton pump inhibitor to be developed as an optical isomer, has demonstrated more effective healing vs. omeprazole and lansoprazole in patients with reflux oesophagitis (RO). However, RO recurs in a high proportion (80%) of these patients within 12 months of initial therapy, highlighting the importance of maintenance treatment. Previous studies have shown esomeprazole to be effective as maintenance therapy in healed RO patients. RO and ⁄ or discontinuation due to symptom r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 27 publications
5
63
0
3
Order By: Relevance
“…The major limitation of our study is the lack of a comparator arm and the openlabel aspect of the trial design. [27][28][29][30] There is limited and controversial evidence that the presence of H. pylori infection may protect against GERD. 31 A recent systematic review confirmed that the prevalence of H. pylori infection is lower in patients with GERD than in those without the disease.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of our study is the lack of a comparator arm and the openlabel aspect of the trial design. [27][28][29][30] There is limited and controversial evidence that the presence of H. pylori infection may protect against GERD. 31 A recent systematic review confirmed that the prevalence of H. pylori infection is lower in patients with GERD than in those without the disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of studies compared distinct PPIs. An updated meta-analysis that added the study by Devault 52 to that of Lauritsen 53 shows that esomeprazole 20 mg is more effective than lansoprazole 15 mg in maintaining endoscopic and clinical remission at 6 months (Fig. 4).…”
Section: B Erosive Esophagitis I) Histamine H2-receptor Antagonistsmentioning
confidence: 96%
“…However some studies suggest that a standard dose PPI could be more effective and less costly for the maintenance of management of GERD [77]. According to a large, randomized study [78] esomeprazole 20 mg is more effective than lansoprazole 15 mg in maintaining remission independently of disease severity.…”
Section: Long-term Management With Ppi Therapymentioning
confidence: 96%